Single Crystal X‐ray Structure of Cu3TaSe4 and a Comparative Study of Cu3MX4 (M = V, Nb, Ta; X = S, Se, Te)1. Issue 5 (12th February 2014) - Ali, Sk Imran; van Smaalen, Sander
Abstract Single crystals of Cu3TaSe4 were obtained by chemical vapor transport with iodine as transport agent. Cu3TaSe4 crystallizes in the sulvanite structure type with space group P <![CDATA[4]]> <inline-graphic xlink:href="ark:/27927/pgg52xccxpw" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />3m and a = 5.6613(3) Å at room temperature. Structure refinements against single‐crystal X‐ray diffraction data result in a Cu–Se distance slightly longer than the Ta–Se distance, whereas previous Rietveld refinements obtained a Cu–Se distance shorter than the Ta–Se distance [G. E. Delgado et al., J. Alloys Comp.2007, 439, 346]. The structural variations of sulvanite type compounds Cu3MX4 (M = V, Nb, Ta; X = S, Se, Te) are discussed in view of small distortions of CuX4 and MX4 tetrahedra and the atomic valences.